2014
DOI: 10.1093/ejcts/ezu184
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive multiple surgical interventions to pulmonary artery sarcoma

Abstract: We describe our experience with a patient who had metastasized pulmonary artery sarcoma, but survived 7 years after diagnosis. A 61-year-old man was diagnosed with pulmonary artery intimal sarcoma after resection of metastatic tumours to the bilateral lungs. The primary lesion in the pulmonary artery trunk extending into the bilateral branches was treated by tumour endoarterectomy followed by chemotherapy. He underwent resections of lung metastases two more times before detection of recurrent obstructive pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Other than chemo-and radiotherapy, a number of reports have found that repeated surgical interventions could also be associated with prolonged survival in patients with recurrence or metastatic PAS. 23,24 In our study, two patients noted to have recurrent disease without metastasis, especially one (patient 11), the oldest example for reoperation as we know, underwent secondary operation successfully at the age of 81.…”
Section: Discussionmentioning
confidence: 63%
“…Other than chemo-and radiotherapy, a number of reports have found that repeated surgical interventions could also be associated with prolonged survival in patients with recurrence or metastatic PAS. 23,24 In our study, two patients noted to have recurrent disease without metastasis, especially one (patient 11), the oldest example for reoperation as we know, underwent secondary operation successfully at the age of 81.…”
Section: Discussionmentioning
confidence: 63%
“…A review of the literature showed 23 cases, of which 15 cases (65%) developed lung metastasis. Other metastasized sites were the pleura, brain, bone, liver, and others with the percentages of 9, 17, 17, 9, and 17%, respectively [2, 6, 13, 14]. Such information, especially concerning the brain, might be useful for careful follow-up of patients with IS.…”
Section: Discussionmentioning
confidence: 99%
“…Intimal sarcoma is a totipotent‐intimal‐cell originated tumour. Pulmonary artery intimal sarcoma arises from the intimal layer of the right, left, or main pulmonary arteries, where pulmonary metastases are common . In extremely rare cases, it may extend in a retrograde manner to the pulmonary valve and right ventricle .…”
Section: Discussionmentioning
confidence: 99%
“…The impact of chemotherapy and radiotherapy remains unclear, although some studies have demonstrated their effectiveness . The use of radiation therapy and chemotherapy after surgical treatment has been found to prolong survival time compared with surgery alone .…”
Section: Discussionmentioning
confidence: 99%